How does Africa’s most hunted bat vary across the continent? Population traits of the straw-coloured fruit bat (Eidolon helvum) and its interactions with humans - Alison J, Peel; James L. N., Wood; Baker, Kate S.; Breed, Andrew C.; de Carvalho, Arlindo; Fernandez-Loras, Andres; Gabrieli, Harrison Sadiki; Gembu, Guy-Crispin; Kakengi, Victor A.; Kaliba, Potiphar M.; Kityo, Robert M.; Tiziana, Lembo; et al. (Acta Chiropterologica, 2017)
The straw-coloured fruit bat, Eidolon helvum, is a common and conspicuous migratory species, with an extensive distribution across sub-Saharan Africa, yet hunting and habitat loss are thought to be resulting in decline in some areas. Eidolon helvum is also a known reservoir for potentially zoonotic viruses. Despite E. helvum’s importance, ecological and behavioural traits are poorly described for this species. Here we present extensive data on the distribution, migration patterns, roost size, age and sex composition of 29 E. helvum roosts from nine countries across tropical Africa, including roosts not previously described in the literature. Roost age and sex composition were dependent on timing of sampling relative to the annual birth pulse. Rather than a single ‘breeding season’ as is frequently reported for this species, regional asynchrony of reproductive timing was observed across study sites (with birth pulses variably starting in March, April, September, November or December). Considered together with its genetic panmixia, we conclude that the species has a fluid, fission-fusion social structure, resulting in different roost ‘types’ at different times of the year relative to seasonal reproduction. Bat-human interactions also varied across the species’ geographical range. In the absence of significant hunting, large urban colonies were generally tolerated, yet in regions with high hunting pressure, bats tended to roost in remote or protected sites. The extensive quantitative and qualitative data presented in this manuscript are also valuable for a wide range of studies and provide an historical snapshot as its populations become increasingly threatened.
Keywords: Age composition; Demography; Fission-fusion; Hunting; Straw-coloured fruit bat